2021
DOI: 10.1155/2021/9971236
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of the Collapse of Necrotic Femoral Head by CT and X-Ray Examinations before Hip Replacement Based on Intelligent Medical Big Data

Abstract: It was to explore the effect of the CT and X-ray examinations before the hip replacement to predict the collapse of the necrotic femoral head under the classification of medical big data based on the decision tree algorithm of the difference grey wolf optimization (GWO) and provide a more effective examination basis for the treatment of patients with the osteonecrosis of the femoral head (ONFH). From January 2019 to January 2021, a total of 152,000 patients with ONFH and hip replacement in the tertiary hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The final consensus of the 2019 Revised ARCO classification for ONFH did not require CT for diagnosing and staging ONFH. Nevertheless, there are some investigators that believe that a CT scan is needed for accurate staging [ [10] , [11] , [12] , [13] , [14] ]. To our knowledge, no study has confirmed the utility of plain radiographs and MRI or evaluated the role of CT scans for the Revised ARCO diagnosis and staging of non-traumatic ONFH using a consecutive cohort of patients over a 10-year period.…”
Section: Introductionmentioning
confidence: 99%
“…The final consensus of the 2019 Revised ARCO classification for ONFH did not require CT for diagnosing and staging ONFH. Nevertheless, there are some investigators that believe that a CT scan is needed for accurate staging [ [10] , [11] , [12] , [13] , [14] ]. To our knowledge, no study has confirmed the utility of plain radiographs and MRI or evaluated the role of CT scans for the Revised ARCO diagnosis and staging of non-traumatic ONFH using a consecutive cohort of patients over a 10-year period.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%